Domestication of the African regional biosafety and biosecurity legislative framework – Lessons learned from the first four countries: Zambia, Botswana, Lesotho, and Sierra Leone - Christine Fortunate Rebecca Mutesi; Talkmore Maruta; Noelina Nantima; Jacqueline Lichoti Kasiiti; Zikan Koroma; Kilinda Imanuel Kilie; Tsaletseng Siimane; Mosito Tsoeunyane; Maruping Maruping; Patrick Masokwane; Samantha Letsholo; Powell Chonga; et al. (Global Security: Health, Science and Policy)
Introduction The Africa Centres for Disease Control and Prevention (Africa CDC) launched the Biosafety and Biosecurity (BBI) Initiative in 2019. The initiative’s main objective is to improve biosafety and biosecurity (BSBS) systems in African Union Member States. This paper presents the initiative’s strategic plan for the next five years, which outlines five priority areas. The plan also emphasises the need for a comprehensive legislative framework to address gaps in AU Member States.Methods The BSBS Legal Framework model was created after extensive strategic consultations and feedback loops, which helped align it with international standards. A systematic and inclusive approach, which considered geographical representation, institutional capacity, and national priorities, was used to adapt the framework to pilot countries like Zambia, Botswana, Lesotho, and Sierra Leone. The drafters of the legislative framework underwent a rigorous training programme to ensure their expertise in BSBS principles.Results During consultative meetings, Africa CDC observed that there were common legislative gaps in the pilot countries. These gaps included the absence of a centralised coordinating entity, the need for comprehensive national standards, and deficiencies in multisectoral risk assessments. As a result of the African Union process, the Regional BSBS legislative framework was endorsed and adopted by AU Executive Council and Assembly. Countries made varying progress in implementing the legislation, addressing the identified gaps, and developing roadmaps for implementation.Discussion Challenges such as resource constraints and coordination issues have highlighted the complex nature of BSBS governance during domestication. Recommendations include strengthening consultative mechanisms, broadening legislative frameworks, and establishing lead entities to enhance coordination.Conclusion To achieve a comprehensive BSBS governance, Africa CDC needs to shift its approach towards a more integrated, coordinated and sustainable strategy. Governments, in collaboration with international partners, should prioritise legislative reforms, establish lead entities and continuously work on capacity-building efforts to strengthen resilience against emerging biological threats. Additionally, they should contribute to a global BSBS network.